2021
DOI: 10.1029/2021jb022082
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Sea Electric and Magnetic Surveys Over Active and Inactive Basalt‐Hosted Hydrothermal Sites of the TAG Segment (26°, MAR): An Optimal Combination for Seafloor Massive Sulfide Exploration

Abstract: Seafloor mineral exploration started decades ago, however technologies were long limited to surface vessels implementing instruments mounted to their hulls, restricting deep-sea research to low-resolution data. At the beginning of the 1990's, the first deep-sea geophysical measurements were carried out by manned submersible DSV Alvin (Tivey et al., 1993) over the active, high-temperature, basalt-hosted hydrothermal site TAG (26°N, Mid-Atlantic Ridge). This seminal study revealed that the active sulfide mound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…More efforts, including but not limited to combined laboratory simulations and field observations, are needed to delineate how others affect the oxidation of SMS deposits. As SMS deposits are considered potential targets for mining (Szitkar et al., 2021; Van Dover, 2019), such knowledge is instructive for understanding the complicated physicochemical properties of SMS deposits, which may ultimately contribute to designing future exploitation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More efforts, including but not limited to combined laboratory simulations and field observations, are needed to delineate how others affect the oxidation of SMS deposits. As SMS deposits are considered potential targets for mining (Szitkar et al., 2021; Van Dover, 2019), such knowledge is instructive for understanding the complicated physicochemical properties of SMS deposits, which may ultimately contribute to designing future exploitation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Migrating electrons produce current in SMS deposits, creating spontaneous "geobattery" (Sato & Mooney, 1960). Seafloor self-potential surveys have shown that SMS deposits in inactive hydrothermal have strong electric anomalies (Szitkar et al, 2021;Zhu et al, 2020) and therefore confirm the existence of galvanic reactions in SMS deposits. Laboratory simulations have verified that galvanic reactions can accelerate the oxidation rates of sulfides (Knight et al, 2018).…”
Section: 1029/2022gc010368mentioning
confidence: 94%
See 1 more Smart Citation
“…In the last decades, galvanometric and electromagnetic methods have been used for the exploration and assessment of SMS resources. These methods include the controlled source electromagnetic (CSEM) method, the direct current (DC) resistivity imaging method, the transient electromagnetic (TEM) method, and the passive self‐potential (SP) method (see case studies in Cairns et al., 1996; Constable et al., 2018; Galley et al., 2021; Gehrmann et al., 2019; Haroon et al., 2018; Ishizu et al., 2019; Kawada & Kasaya, 2018; Müller et al., 2018; Su, Tao, Shen et al., 2022; Szitkar et al., 2021; Zhu et al., 2020). However, ore bodies and metallic deposits are not always characterized by conductivity contrasts (Mao & Revil, 2016; Mao et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kasaya et al (2020) successfully conducted marine DC resistivity and SP surveys in hydrothermal deposit areas using two AUVs. Deep-sea passive electric measurements combined with high-resolution magnetic measurements based on AUV were also used in SMS exploration (Szitkar et al, 2021). However, the above investigations are all used for the delineation of SMS deposits at the seafloor.…”
Section: Introductionmentioning
confidence: 99%